Rosalía de Castro's El caballero de las botas azules and Charles Perrault's Le chat botté : Parody, Critique and a New Social (Dis)order. - Kana, Aviva (Hispanic Review)
This article examines Rosalía de Castro's novel El caballero de las botas azules as a creative parody of Charles Perrault's Le chat botté. In it, I argue that the novel demonstrates de Castro's radical ideas about gender roles and the stagnation of 19th-century Castilian society through its dialogue with Perrault's tale, showing how de Castro's novel is an inverted parody of Perrault's fairy tale that advocates for societal change instead of protecting the status quo. The parody becomes clearer through de Castro's ironic recreation of the characters from Puss in Boots, transforming them into transgressive figures that interrogate traditional ideas of masculinity and femininity. The novel also parodies the moralistic tone of fairy tales by insisting that people need to "bell the cat" and address toxic social norms head on, essentially promoting the idea of revolution.